2011
DOI: 10.1109/jsac.2011.111003
|View full text |Cite
|
Sign up to set email alerts
|

Topology Discovery at the Router Level: A New Hybrid Tool Targeting ISP Networks

Abstract: Abstract-For a long time, traceroute measurements combined with alias resolution methods have been the sole way to collect Internet router level maps. Recently, a new approach has been introduced with the use of a multicast management tool, mrinfo, and a recursive probing scheme. In this paper, after analyzing advantages and drawbacks of probing approaches based on traceroute and mrinfo, we propose a hybrid discovery tool, MERLIN (MEasure the Router Level of the INternet), mixing mrinfo and traceroute probes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
(51 reference statements)
0
28
0
Order By: Relevance
“…In some cases, it can be very useful: almost 30% of alias pairs were obtained with this method on AS10010 on April 14 th , 2017. 11 Moreover, since not all interfaces of a router partially discovered through the address-based method will reply to 10 Transit filtering has already been observed for IGMP probing [12]. 11 See https://github.com/JefGrailet/treenet/tree/master/v3/Measurements/ UDP, we can rely on the IP-ID-based methods (when possible) to build a larger, more accurate alias.…”
Section: Alias Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, it can be very useful: almost 30% of alias pairs were obtained with this method on AS10010 on April 14 th , 2017. 11 Moreover, since not all interfaces of a router partially discovered through the address-based method will reply to 10 Transit filtering has already been observed for IGMP probing [12]. 11 See https://github.com/JefGrailet/treenet/tree/master/v3/Measurements/ UDP, we can rely on the IP-ID-based methods (when possible) to build a larger, more accurate alias.…”
Section: Alias Resolutionmentioning
confidence: 99%
“…In particular, we focus on active techniques (i.e., done at the same time as traceroute or shortly after, with additional probing) rather than passive approaches. Such approaches range from analytical methods like in-depth analysis of traceroute records, as implemented in kapar [9], to lightweight probing like IGMP probing [11]. The latter has the advantage of silently collecting all multicast interfaces of a router in a single probe.…”
Section: Introductionmentioning
confidence: 99%
“…It only processes the first packets (there is no continuation . Merlin global overview [120] flag forcing the wait for the remaining fragments). Mérindol et al have observed this behavior on large degree CISCO routers.…”
Section: Merlinmentioning
confidence: 99%
“…If Merlin is still based on recursive IGMP probing, it also improves mrinfo and mrinfo-rec by probing from several vantage points, each one being managed by a central server [120], in order to increase the exploration coverage while limiting the probing redundancy. Fig.…”
Section: Merlinmentioning
confidence: 99%
See 1 more Smart Citation